Gender-specific associations between neutrophil levels and refracture risks: a retrospective cohort study - Yuan, Shuai; Zhou, Xiao-jie; Jiao, Hao-tian; Gong, Ya-qin; Jin, Jian; Cao, Yan; Lu, Ke; Li, Chong (Frontiers in Endocrinology, 2026)
BackgroundOsteoporotic fractures (OPFs) significantly impact global health, predominantly affecting individuals over 50 years old. Furthermore, it has high incidence and refracture rates. Currently, the association between neutrophil (NEU) levels and the risk of recurrent fractures is still undetermined. Therefore, this study investigated the association between NEU levels at hospital admission and recurrent fracture risk in OPF patients.MethodsThis retrospective cohort study analyzed 2,474 OPF patients who underwent surgical intervention at the Affiliated Kunshan Hospital of Jiangsu University between 2018 and 2023. The data were acquired from the hospital’s Osteoporotic Fracture Registration System. Patients’ NEUs were measured at admission, and they were followed up for recurrent fractures. Statistical assessments were carried out via Cox proportional hazards regression models to elucidate 5-year refracture risk. The nonlinear relationships were determined by smooth curve fitting and threshold analyses.ResultsThe results showed a significant sigmoidal (non-linear) relationship between the risk of recurrent fractures and NEU counts in male patients. Furthermore, NEU levels ranged between 4.4 - 8.5 ×109/L indicated a substantially reduced risk of refractures (95% CI = 0.37 - 0.86; HR = 0.57; P-value = 0.008). Moreover, there were no substantial associations between NEU levels and refracture rates in the female cohort across all models.ConclusionsThis study indicated a significant sigmoidal correlation between NEU levels and refracture risk in male OPF patients, ranging from 4.4 to 8.5 ×109/L. Further research is required to elucidate these mechanisms and assess the clinical application of NEU levels as a biomarker for refracture risk in males.